2021
DOI: 10.1126/scitranslmed.abe5640
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation states drive glucose uptake and FDG-PET alterations in neurodegenerative diseases

Abstract: FDG-PET shows that microglial activation might drive cerebral glucose uptake in mice and patients with AD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
121
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(141 citation statements)
references
References 74 publications
16
121
1
3
Order By: Relevance
“…[ 18 F]FDG accumulates in brain tissue according to facilitated transport and hexokinase-mediated phosphorylation. The uptake of [ 18 F]FDG also depends on the consumption of glucose by the astrocytes in interaction with neuronal function [1], on the transport mediated by the glucose transporter 1 (GLUT-1) across the blood-brain barrier [2], and possibly during pathological inflammatory conditions on microglial activation states [3]. Currently, [ 18 F]FDG-PET, which is widely available in Europe, is the most accurate in vivo method for the investigation of regional human brain metabolism in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FDG accumulates in brain tissue according to facilitated transport and hexokinase-mediated phosphorylation. The uptake of [ 18 F]FDG also depends on the consumption of glucose by the astrocytes in interaction with neuronal function [1], on the transport mediated by the glucose transporter 1 (GLUT-1) across the blood-brain barrier [2], and possibly during pathological inflammatory conditions on microglial activation states [3]. Currently, [ 18 F]FDG-PET, which is widely available in Europe, is the most accurate in vivo method for the investigation of regional human brain metabolism in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…NO production from microglia is reportedly dependent on glucose as an energy source [ 122 ]. However, the metabolic pathway of glucose as an energy source for microglial function remains largely unknown [ 123 , 124 , 125 ]. Energy metabolism in inflammatory M1 microglia is believed to shift from oxidative phosphorylation in mitochondria to the glycolytic system [ 126 , 127 , 128 ], suggesting that PPP flux, a shunt pathway of the glycolytic system, might be enhanced in inflammatory M1 microglia.…”
Section: Issues To Be Resolved In the Futurementioning
confidence: 99%
“…2F,G). Recent study by Xiang et al (2021) showed that [ 18 F]FDG uptake reflected metabolism derived from microglia and that the increased [ 18 F]FDG might instead due to microglia activation.…”
Section: Metabolism Imagingmentioning
confidence: 99%
“… Brendel et al (2019) demonstrated a reduced [ 18 F]FDG uptake in brain of hTau mice compared to wild-type mice and that treatment using novel aggregation-inhibiting oligomer modulator Anle138b can rescue this reduction in [ 18 F]FDG measures at follow-up scan after treatment ( Figures 2F,G ). Recent study by Xiang et al (2021) showed that [ 18 F]FDG uptake reflected metabolism derived from microglia and that the increased [ 18 F]FDG might instead due to microglia activation.…”
Section: Metabolism Imagingmentioning
confidence: 99%